Discord and Consensus in the Low Countries, 1700-2000 - Tiedau, Ulrich; Fenoulhet, Jane; Quist, Gerdi (Global Dutch, 2016)
All countries, regions and institutions are ultimately built on a degree of consensus, on a collective commitment to a concept, belief or value system. This consensus is continuously rephrased and reinvented through a narrative of cohesion and challenged by expressions of discontent and discord. The history of the Low Countries is characterised by both a striving for consensus and eruptions of discord, both internally and from external challenges. This interdisciplinary volume explores consensus and discord in a Low Countries context along broad cultural, linguistic and historical lines. Disciplines represented include early-modern and contemporary history; art history; film; literature; and translation scholars from both the Low Countries and beyond.